Synthesis and Characterization of Polysaccharide Based Hydrogels for removal of Mercury Ion from Aqueous Solution - Samandari, Samaneh Saber (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Production of major industrial products may degrade the environment. It can result in water pollution since it produces pollutants such as water-coloring agents and toxic heavy metals that are extremely harmful and impair the environment even at low concentrations. To reduce the risk of environmental pollution from these wastes, it is necessary to treat them prior to discharging into the environment. The adsorption process onto solid substrate and natural polymeric materials especially polysaccharides is considered superior to other removal techniques. Mercury deserves special attention among heavy metals such as cadmium, cobalt, chromium, copper, lead, nickel, and zinc, which are highly toxic and dangerous. Mercury spillage is highly dangerous because it destroys brain tissue, lungs, and has the ability to distort protein leading to toxic effects; it mainly affects the kidney and nerve system and may cause some disorders and diseases. Therefore, the removal of mercury from aqueous solutions, especially drinking water, is very important in hydrometallurgical and wastewater treatment. The main aim of this thesis is to investigate the mercury ion removal ability of different natural polymers, cellulose, chitosan, and pullulan. For this purpose, acrylamide monomer has been grafted to chitosan, cellulose, and pullulan and three different hydrogels were synthesized. In addition, the cellulosegraft-polyacrylamide/nano-hydroxyapatite composite hydrogel and pullulan-graftpolyacrylamide porous hydrogels were prepared and characterized using FTIR and SEM. Then, the effects of several variables such as time, temperature, and pH on the swelling behavior of the hydrogels were examined. The results showed that the cellulose-graft-polyacrylamide hydrogel with 5170 % has the maximum and pullulan-graft-polyacrylamide hydrogel with 1554 % has the minimum swelling amount. In addition, the swelling amount of all hydrogels significantly changed with temperature and pH and the kinetics of swelling of hydrogels were best fitted with the second-order model. Finally, the adsorption studies of the mercury (II) ions on synthesized hydrogels were performed to investigate their uptake performances. The results showed that the maximum mercury ion adsorption by cellulose-graft-polyacrylamide hydrogel (1.93 g.g -1 ), cellulose-graft-polyacrylamide/hydroxyapatite composite hydrogel (1.99 g.g1 ), chitosan-graft-polyacrylamide hydrogel (1.87 g.g-1 ), pullulan-graftpolyacrylamide hydrogel (1.75 g.g-1 ), and pullulan-graft-polyacrylamide porous hydrogel (1.78 g.g-1 ) were attained after 24 h. In addition, batch adsorption experiments in different conditions such as temperature, pH, mercury solution concentration, with different amount of adsorbent were performed. According to the results, all synthesized hydrogels are temperature, pH and concentration sensitive. In addition, the kinetic, isotherm, and the thermodynamic parameters of adsorption were calculated. The results indicated that adsorption of mercury ions on all hydrogels followed pseudo-second-order kinetics and best fitted with Langmuir adsorption isotherm with the highest maximum adsorption (qmax) of Hg(II) ions for composite hydrogel and the lowest for pullulan based hydrogels. The negative value of free energy change (ΔGº) and positive value of enthalpy change (ΔHº) shows the adsorption process is spontaneous and endothermic. Finally, the regeneration ability of hydrogels through desorption of mercury ions for three adsorption/desorption cycles were examined. It can be concluded that the synthesized hydrogels qualified for practical application since they can be used repeatedly with negligible loss of adsorption capacity for the mercury ions. Keyword: Cellulose, chitosan, pullulan, hydroxyapatite, hydrogel, porous hydrogel, composite hydrogels, water treatment, mercury

Öz: Büyük sanayi ürünlerinin üretimi çevreyi olumsuz etkileyebilmektedir. Su renklendirici maddelerle son derece zararlı ve düşük konsantrasyonlarda bile çevreyi bozan zehirli ağır metaller gibi kirletici ürünler su kirliliğinin nedenidir. Bu atıklardan oluşan çevre kirliliği riskini azaltmak için,çevreye salınımları öncesi onları gidermek gerekir.Katı yüzey ve doğal polimerik malzemeler, özellikle polisakkaritler üzerine adsorpsiyon işlemi diğer giderim tekniklerine göre üstün kabul edilir. Civanın son derece zehirli ve tehlikeli olan kadmiyum, kobalt, krom, bakır, kurşun, nikel, ve çinko gibi ağır metaller arasında dikkate değer bir yeri vardır. Civa beyin dokusu, akciğerleri tahrip ve protein bozucu toksik etkiye sahiptir, Ana etkisi ile ağırlıklı olarak böbrek ve sinir sistemini etkileyerek bazı bozukluklar ve hastalıklara neden olabilir. Bu nedenle, sulu çözeltilerden civa, özellikle içme suyu için, hidrometalurjik ve atık sulardan arıtımı son derece önemlidir. Bu tezin temel amacı, selüloz, kitosan ve pullulan gibi farklı doğal polimerlerin civa iyonu giderme yeteneği araştırmaktır. Bu amaçla, akrilamid monomerin kitosan, selüloz ve pullulana aşılanarak ve üç farklı hidrojeller sentezlenmiştir. Buna ek olarak selüloz-aşı-poliakrilamid/nanohidroksiapatat kmposit hidrojeli ve pullulan-aşı-poliakrilamid poroz hidrojelleri hazırlanarak FTIR v SEM kullanarak karakterize edilmişlerdir. Daha sonra, bu hidrojeller şişme davranışına karşın zaman, sıcaklık ve pH gibi çeşitli değişkenlerin etkileri incelenmiştir. Sonuçlar selüloz-greft-poliakrilamid hidrojelinin % 5170 şişme değeri ile maksimum, pululan-greft-poliakrilamid hidrojelinin ise %1554 değerle minimum şişme yüzdesi değerine sahip olduğunu göstermiştir. Buna ek olarak, tüm hidrojellerin şişme miktarı ısı ve pH ile önemli ölçüde değişimiş ve hidrojellerin şişme kinetiği ikinci dereceden modeline uygunluk göstermiştir. Son olarak, sentezlenen jellerin cıva (II) iyonlarının adsorpsiyon çalışmaları onların tutma performanslarını araştırmak için yapılmıştır. Araştırma sonucunda, 24 saatlik etkileşim süresi sonucundaki maksimum civa tutma kapasiteleri selüloz-aşı- poliakrilamid hidrojeli (1.93g.g-1 ), selüloz-aşı-poliakrilamid /hidroksiapatat kompozit hidrojeli (1.99 g.g-1 ), kitosan-aşı-poliakrilamid hidrojeli (1.87 g.g-1 ), pululan-aşı- poliakrilamid hidrojeli (1.75 g.g-1 ), ve pululan-aşı-poliakrilamid poroz hidrojeli (1.78 g.g -1 ) olarak belirlenmiştir. Buna ek olarak, batch adsorpsiyon deneyleri adsorbentin farklı bir miktarı ile, sıcaklık, pH, civa çözelti konsantrasyonlarının etkileşimleriyle gerçekleştirilmiştir. The negative value of free energy change (ΔGº) and positive value of enthalpy change (ΔHº) shows the adsorption process is spontaneous and endothermic. Elde edilen sonuçlara göre, tüm hidrojel sıcaklık, pH ve konsantrasyona duyarlıdır. Buna ek olarak,adsorpsiyonun, kinetik, izoterm ve termodinamiği hesaplandı. Sonuçlar tüm hidrojellerin üzerinde civa iyonların tutunmalarının yalancı-ikincidereceden kinetiği takip ettiğini ve Langmuir adsorpsiyon izotermiyle civa adsorpsiyonun (qmax) en yüksek değerinin kompozit hidrojeli ile en düşük değerinin pululan bazlı hidrojelle olduğu belirlenmiştir. Serbest enerji değişimi (ΔGº) negatif ve entalpi değişimi (ΔHº) pozitif değeri adsorpsiyon işleminin kendiliğinden ve endotermik olduğunu göstermektedir. Son olarak, üç kez adsorpsiyon / desorpsiyon döngüsü ile civa iyonları desorpsiyon yoluyla hidrojellerin yenilenmesi yeteneği incelenmiştir. Bu da, civa iyonları için adsorpsiyon kapasitesinin göz ardı edilebilir kayıp değerinde olması nedeniyle tekrar tekrar kullanılabilmesi özelliğini ortaya çıkarmakta ve hidrojelin pratik uygulama için nitelikli olduğu sonucuna varılabilmektedir. Anahtar Kelimeler: Selüloz, kitosan, pullulan, hidroksiapatat, hidrojel, poroz hidrojel, kompozit hidrojel, su iyleştirme, civa
Doctor of Philosophy in Chemistry. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Cellulose; chitosan; pullulan; hydroxyapatite; hydrogel; porous hydrogel; composite hydrogels; water treatment; mercury